2020
DOI: 10.1194/jlr.ra120001022
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive sphingolipid patterns in chronic multiple sclerosis lesions

Abstract: Multiple sclerosis (MS) is a CNS disease characterized by immune-mediated demyelination and progressive axonal loss. MS-related CNS damage and its clinical course have two main phases: active and inactive/progressive. Reliable biomarkers are being sought to allow identification of MS pathomechanisms and prediction of its course. The purpose of this study was to identify sphingolipid (SL) species as candidate biomarkers of inflammatory and neurodegenerative processes underlying MS pathology. We performed sphing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…There is some evidence from previous studies in mice and humans that ceramides are increased in EAE [33,55] and MS [50,56,57] and contribute to the disruption of the BBB [21,58]. In a study using knockout mice or inhibition of acidic sphingomyelinase (ASM), it was suggested that high levels of ceramides are caused by over-activation of ASM [59,60], which produces ceramides in the lysosome via sphingomyelin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence from previous studies in mice and humans that ceramides are increased in EAE [33,55] and MS [50,56,57] and contribute to the disruption of the BBB [21,58]. In a study using knockout mice or inhibition of acidic sphingomyelinase (ASM), it was suggested that high levels of ceramides are caused by over-activation of ASM [59,60], which produces ceramides in the lysosome via sphingomyelin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that lipid signatures can reveal potential biomarkers associated with disease progression, as well as provide novel information about pathomechanisms involved in progressive MS. Targeted sphingolipidomics have been employed to establish comprehensive SL profiles in chronic MS lesions [ 128 ]. Interestingly, our data on ex vivo SL analysis of postmortem tissues obtained from individuals with clinically diagnosed MS indicated distinctive lipid profiles in chronic MS lesions.…”
Section: Ms Progressionmentioning
confidence: 99%
“…HexCers and SHexCers are structural lipids of myelin membrane and enriched in mature oligodendrocytes . In humans, the brain levels of HexCer and SHexCer (measured in the CSF) change during brain aging and in a number of pathological conditions such as multiple sclerosis, Alzheimer’s disease, and Parkinson’s disease. …”
Section: Discussionmentioning
confidence: 99%